Предмет: Алгебра, автор: gammersmidtmarana

3(4 - 2x) + 6 = - x + 4
Помогите прошууу


kira2363: мало балов я б помогла б

Ответы

Автор ответа: Аноним
1

Ответ:Let's simplify the left side of the equation first by using the distributive property:

3(4 - 2x) + 6 = 12 - 6x + 6

Now we can rewrite the equation as:

12 - 6x + 6 = -x + 4

Next, let's group the x terms on one side and the constants on the other side by subtracting 6 from both sides:

12 - 6x + 6 - 6 = -x + 4 - 6

Simplifying both sides, we get:

6 - 6x = -x - 2

Let's get all the x terms on one side and the constants on the other side by adding 6x and 2 to both sides:

6 - 6x + 6x + 2 = -x - 2 + 6x + 2

Simplifying both sides, we get:

8 = 5x

Finally, we can solve for x by dividing both sides by 5:

x = 8/5 or x = 1.6

Therefore, the solution to the equation 3(4 - 2x) + 6 = -x + 4 is x = 8/5 or x = 1.6.

Объяснение:

Похожие вопросы
Предмет: Физика, автор: MakarovaLerra